2018
DOI: 10.1088/1361-648x/aad5af
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic irreversibility in VO2/Ni bilayers

Abstract: We studied the temperature dependence of the magnetic properties of VO/Ni bilayers. The Ni films were deposited on either monoclinic or rutile phase VO. The temperature induced VO transformation from a monoclinic to a rutile structure induces strain in the Ni film. Due to an inverse magnetoelastic effect the coercivity of the Ni films is strongly modified. Both Ni films show strong enhancement of the coercivity near the transition temperature. The coercivity enhancement of Ni is associated with the phase coexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Interestingly, the M ‐ T curve shows an abnormal valley in the temperature range where the resistance of VO 2 drops intensely. This phenomenon can be explained by the phase coexistence of the nonmagnetic layer (for example, the VO 2 layer in this work) . The uniform phase change of VO 2 can enhance the magnetization in a gradual way.…”
Section: Strain Analysis and Mechanism Explanationmentioning
confidence: 74%
“…Interestingly, the M ‐ T curve shows an abnormal valley in the temperature range where the resistance of VO 2 drops intensely. This phenomenon can be explained by the phase coexistence of the nonmagnetic layer (for example, the VO 2 layer in this work) . The uniform phase change of VO 2 can enhance the magnetization in a gradual way.…”
Section: Strain Analysis and Mechanism Explanationmentioning
confidence: 74%
“…In thin film form, the FE and AF order parameters of multiferroics could be affected for the phenomenon of magnetostriction [1]- [4] due to the change in the dimensions of the material as a consequence of stresses generated at the contact interface, either with the substrate or with another material. To study this mechanism of coupling at the interface with BFO, the vanadium dioxide (VO2) system was used, which has been widely analyzed due to the structural change it undergoes from VO2 (monoclinic) to VO2 (tetragonal) at a temperature of 340 K, showing weak ferromagnetic behavior [6], [7]. The combination of these materials in heterostructures gives access to the study of mixed properties and their control.…”
Section: Introductionmentioning
confidence: 99%
“…Good compatibility might therefore be expected in the bilayer system based on BFO and VO2 since the interface effects are predominant and detectable in analogous materials [8]. de la Venta et al, [6], [7], [9], [10] showed the change in the coercivity of thin films of nickel deposited on V2O3 and VO2, a change attributed to the structural phase transition of V2O3 and VO2. Saerbeck et al, [11] studied and compiled information about the coupling between magnetism and the structural phase transition by interfacial tension in different systems of La0.7A0.3MnO3 (A = Sr,Ca), Fe3O4, CoFe2O4, FeRh, Ni, Fe and Co, using as a base the structural change in the VO2, V2O3 and BaTiO3 compounds, resulting in structures with hybrid properties that manage to modify and/or control the magnetic behavior through effects of tension and inverse magnetostriction.…”
Section: Introductionmentioning
confidence: 99%
“…To study this mechanism of coupling at the interface with BFO, the vanadium dioxide (VO 2 ) system was used, which has been widely analyzed due to the structural change it undergoes from VO 2 (monoclinic) to VO 2 (tetragonal) at a temperature of 340 K, showing weak ferromagnetic behavior [ 12 , 13 ]. The combination of these materials in heterostructures gives access to the study of mixed properties and their control.…”
Section: Introductionmentioning
confidence: 99%